Profiles of victimized outpatients with severe mental illness in India - Akanksha Rani; K Janaki Raman; Sojan Antony; Ammapattian Thirumoorthy; Chethan Basavarajappa (Wolters Kluwer Medknow Publications, 2023)
Persons with severe mental illness (PwSMI) are at risk of being victimized due to persistent cognitive, emotional, and behavioral symptoms, which can become potential threats for effective reintegration into the community. A total of 217 PwSMI, receiving outpatient psychiatric treatment from a tertiary hospital, were screened for abuse, and if they were identified as abuse, then information about contextual factors contributing to abuse, sociodemographic, family, and clinical and legal profiles was created. Overall, 150 PwSMI were victimized, of which 56% were females, 50.7% were married, 20.7% were educated up to middle school, and 31.4% were homemaker. The most common form of diagnosis was schizophrenia (43.3%), with a mean duration of illness of 14 years. All the victimized PwSMI were subjected to emotional abuse. PwSMI were more likely to be victimized by multiple family members due to poor knowledge and understanding about illness (24%). The majority of the PwSMI had disclosed abuse (62.7%) to nonformal sources (33.3%) with no documentation in the clinical file (82.7%). PwSMI experience ongoing abuse and are more likely to be re-victimized, which increases the need for regular screening and culturally sensitive and comprehensive community-coordinated care and support.